Rola zasobów nierzeczowych w tworzeniu potencjału konkurencyjności obszaru na rynku turystycznym - Nawrocka, Elżbieta (The Role of Nonmaterial Resources in the Competitive Potential Construction of an Area on the Tourist Market, 2008)
Contemporary society has entered the new epoch, namely the period focused on information (the construction of the information society), diversified structures and partitioned culture, while in economy one can observe the relations among nonmaterial resources, productivity and competitiveness of the tourist reception area. The objective of the hereby article is to identify resources which in present tourist environment conditions create the leading competitive potential power of the tourist reception area (referred to in the content as ORT). The first part of the article indicates major changes in the tourist environment, the significantly changing conditions of the competitive potential construction at the tourist market. The following part identifies and interprets the role of nonmaterial resources in creating competitiveness in the new environmental conditions, as well as the ways of their proper application. The final part of the article presents conclusions regarding the most important factors, which facilitate the increasing competitiveness by taking the advantage of nonmaterial resources. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 29, s. 78-86